2015
DOI: 10.1002/jsfa.7362
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide as stunning/killing method on farmed Atlantic salmon (Salmo salar): effects on lipid and cholesterol oxidation

Abstract: The quality of salmon fillets just after slaughtering and after 14 days of refrigerated storage at 2.5 °C did not change, irrespective of the killing method adopted, suggesting that the CO method may be applied without any detrimental effect on the quality of fish fillets. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…PUFAω6 fraction was strongly negatively correlated with primary and secondary oxidation products (CDs: p<0.01; TBARS: p<0.05), whereas ω3 FAs were strongly positively related to CDs (p<0.01) and TBARS (p<0.01). These correlations were in line with the correlation found by Secci et al (2015). Indeed, ω3 fatty acids contribute to quality deterioration and decreases marketability of fish products leading to a major lipid oxidation.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…PUFAω6 fraction was strongly negatively correlated with primary and secondary oxidation products (CDs: p<0.01; TBARS: p<0.05), whereas ω3 FAs were strongly positively related to CDs (p<0.01) and TBARS (p<0.01). These correlations were in line with the correlation found by Secci et al (2015). Indeed, ω3 fatty acids contribute to quality deterioration and decreases marketability of fish products leading to a major lipid oxidation.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Data in the literature indicate that stress during slaughter decreases the oxidative stability of farmed rainbow trout after 165 days of storage at −10 °C . In contrast, no effects of the stunning/killing procedures on lipid oxidation were observed on Nile tilapia and on farmed Atlantic salmon fillets – the latter stored for 14 days at 4 °C . Concerning protein oxidation, the authors found that stunning/slaughtering procedures had no effect on myofibrillar proteins, such as myosin, after 5 months at −18 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, carbon monoxide is an emerging stunning/slaughtering procedure (CO), which has been successfully tested on Atlantic salmon ( Salmo salar Linnaeus 1758) and rainbow trout . In both trials, CO clearly improved animal welfare when compared to the common methods such as percussion or asphyxia in air.…”
Section: Introductionmentioning
confidence: 99%
“…Although three fish group showed lower values, AI and TI of wild and cultured brown trouts were higher than that of Atlantic salmon (P<0.05). Secci et al (2015) reported that AI and TI values for Atlantic salmon were respectively 0.22 and 0.13. The AI values were the same as current study.…”
Section: Lipid Quality Indicesmentioning
confidence: 99%